Clicking vs. Dragging. - Sikkel, Dirk; Steenbergen, Reinder; Gras, Sjoerd (Public Opinion Quarterly)
Web interviewing offers more and more response formats, available in commercial packages for most researchers. But does varying those formats increase respondent engagement while maintaining validity and reliability? To answer that question, we compare seven different techniques for web interviewing. For each technique there is a clicking version, where a respondent clicks on a response category, and a dragging version, where an answer is given by dragging an object. In a test-retest experiment, for five out of seven dragging formats, the psychometric properties appeared to be acceptable. However, the initial advantages of the dragging formats faded away in the retest. Consequently, dragging formats increase respondent engagement only if they are used sparingly.